Personas based support tool for requirements elicitation - Bavani, Mehrnaz Kazemi; Ahmad, Rodina (2009)
Lack of user understanding can bring a damaging effect to software development projects. As we acknowledge, there is a wide variety of users in each software project and consequently there are variation of goals, needs and attitudes within the establishment of users' requirements.So, there are difficulties in organizing and categorizing these information and also, in validating these requirements within a development project. Using personas to capture and analyze users can facilitate user’s understanding.However, identifying personas from large user information is difficult.This research examines the persona technique and proposes a software support tool to help developers in gathering and analyzing requirements by using personas.Likewise, the goals and tasks of each persona are established via actual requirements of the users.The creation and utilization of persona have been investigated via proposed tool aimed to elicit and represent users' requirements in a manageable format. A “Personas based Support Tool for Requirements Elicitation (PSTRE)” facilitates software developers to gather and analyze user requirements.The resulting personas which are suggested by the proposed tool, have to be well understood and well presented to the development team and also provide easy way to extract main functionalities and features of the proposed system.